2010
DOI: 10.1192/bjp.bp.108.062984
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for borderline personality disorder: Cochrane systematic review of randomised trials

Abstract: The current evidence from randomised controlled trials suggests that drug treatment, especially with mood stabilisers and second-generation antipsychotics, may be effective for treating a number of core symptoms and associated psychopathology, but the evidence does not currently support effectiveness for overall severity of borderline personality disorder. Pharmacotherapy should therefore be targeted at specific symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
2
32

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 367 publications
(248 citation statements)
references
References 51 publications
5
200
2
32
Order By: Relevance
“…In this study, little evidence was found for the value of several commonly prescribed antidepressants in BPD, including SSRIs, mianserin and the monoamine oxidase inhibitor, phenelzine. The only antidepressant medication shown to have a positive effect on BPD symptoms outside episodes of major depression was amitriptyline, a tricyclic antidepressant [Lieb et al 2010]. However the use of amitriptyline in BPD, a condition associated with a substantial risk of impulsive selfharm, is limited by its severe toxicity in overdose.…”
Section: Antidepressantsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, little evidence was found for the value of several commonly prescribed antidepressants in BPD, including SSRIs, mianserin and the monoamine oxidase inhibitor, phenelzine. The only antidepressant medication shown to have a positive effect on BPD symptoms outside episodes of major depression was amitriptyline, a tricyclic antidepressant [Lieb et al 2010]. However the use of amitriptyline in BPD, a condition associated with a substantial risk of impulsive selfharm, is limited by its severe toxicity in overdose.…”
Section: Antidepressantsmentioning
confidence: 99%
“…However, the common occurrence of adverse side effects in this class of medications means that they are often preferred for the treatment of acute relapses only [Díaz-Marsá et al 2008;Newton-Howes and Tyrer, 2003;Benedetti et al 1998;Teicher et al 1989]. The most commonly studied antipsychotic, olanzapine, has been found to reduce impulsivity, hostility, affective instability and psychotic symptoms in BPD [Lieb et al 2010;Soler et al 2005;Zanarini et al 2004;Bogenschutz and Nurnberg, 2004;Hallmayer, 2003], although it is associated with metabolic side effects, which may limit its tolerability [Reynolds and Kirk, 2010;Kantrowitz and Citrome, 2008]. A more limited literature supports the use of aripiprazole and haloperidol in BPD, the latter especially for symptoms of anger [Lieb et al 2010].…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%
See 3 more Smart Citations